Effects of lactation number and different stage of lactation on milk yield of Indigenous and Crossbred cows in Bangladesh (International Journal of Natural Sciences, 2011)
A total of 54 samples were collected from 18 milking cows from which nine were indigenous and nine were crossbred to evaluate the effects of different lactation number and different stage of lactation on the milk yield. The average daily milk yield of indigenous and crossbred cows at 1st, 2nd and 3rd lactation were 1.311, 1.633, 2.072 and 8.917, 9.567, 10.167 liter/day/cow respectively and represented the significant difference (p